2021
DOI: 10.11604/pamj.2021.38.92.24462
|View full text |Cite
|
Sign up to set email alerts
|

Mésothéliome malin de l´ovaire: à propos d´un cas

Abstract: Le mésothéliome malin primitif de l´ovaire (MMPO) est une tumeur extrêmement rare qui peut se développer à partir des cellules mésothéliales. Cette néoplasie est causée principalement par une exposition à l´amiante ou à d´autres agents cancérigènes. Un bilan d´extension préopératoire comportant une tomodensitométrie, une imagerie par résonance magnétique et une tomographie par émission de positons est essentiel pour la stadification de la maladie. Le diagnostic positif anatomopathologique repose sur un panel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In 1983, Addis et al reported a 67-year-old white woman with a large tumour of the left ovary, complaining of nausea, upper abdominal pain and biliary regurgitation, and was diagnosed as papillary mesothelioma of ovary (3). Sun et al reported that a 50year-old woman found a hypermetabolic mass in the left ovary by 18 F-FDG PET/CT, and was diagnosed as ovarian mesothelioma pathologically after biopsy in 2019 (4).Another study reported a female patient with ovarian mesothelioma who underwent surgery complemented by adjuvant chemotherapy, with complete radiation response and a disease-free survival time of 1 year (5). In Clement et al's study, 9 cases of mesothelioma presenting as ovarian masses were described, of which at least 2 cases were to be primary in the ovary (6).…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, Addis et al reported a 67-year-old white woman with a large tumour of the left ovary, complaining of nausea, upper abdominal pain and biliary regurgitation, and was diagnosed as papillary mesothelioma of ovary (3). Sun et al reported that a 50year-old woman found a hypermetabolic mass in the left ovary by 18 F-FDG PET/CT, and was diagnosed as ovarian mesothelioma pathologically after biopsy in 2019 (4).Another study reported a female patient with ovarian mesothelioma who underwent surgery complemented by adjuvant chemotherapy, with complete radiation response and a disease-free survival time of 1 year (5). In Clement et al's study, 9 cases of mesothelioma presenting as ovarian masses were described, of which at least 2 cases were to be primary in the ovary (6).…”
Section: Introductionmentioning
confidence: 99%